Adsorption behaviors of Cu2+, Zn2+ and Cd2+ onto proteins, humic acid, and polysaccharides extracted from sludge EPS: Sorption properties and mechanisms. (November 2019) - Wei, Liangliang; Li, Jianju; Xue, Mao; Wang, Sheng; Li, Qiaoyang; Qin, Kena; Jiang, Junqiu; Ding, Jing; Zhao, Qingliang
Graphical abstract: Highlights: Protein/humic acid were more efficient in Zn 2+ and Cd 2+ sorption than polysaccharides. Noticeable electrostatic interaction occurred for proteins/humic acid adsorption. Freundlich model for Cu 2+ /Cd 2+ sorption while Langmuir for Zn 2+ on polysaccharide/HA. Metals sorption on EPS was exothermic process, especially for humic acid and proteins. Abstract: To clarify the adsorption behaviors of typical heavy metals onto sludge extracellular polymeric substances (EPS), the adsorption capacities and mechanisms, as well as the contributions of the different EPS components (proteins, humic acids and polysaccharides), to the adsorption of Zn 2+, Cu 2+ and Cd 2+ were separately explored. Overall, proteins exhibited a relatively high adsorption capacity for the three metals ions, followed by humic acid, whereas least for polysaccharides. The adsorption of Cu 2+ and Cd 2+ onto proteins, humic acid and polysaccharides fit well to the Freundlich isotherm, whereas Langmuir model was the best fit for Zn 2+ bindings onto polysaccharides/humic acid. The binding of Cu 2+, Zn 2+ and Cd 2+ onto the three EPS components was exothermically favorable, and significant electrostatic interactions were observed for the heavy metals sorption onto humic acid and proteins. In addition, the effect of metal ions sorption on the spectrum of the proteins, polysaccharides and humic acid was also explored.